Characterization of Escherichia coli Strains from Cases of Childhood Diarrhea in Provincial Southwestern Nigeria - Okeke, Iruka N. (American Society for Microbiology, 2000)
In a study carried out in small-town and rural primary health care centers in southwestern Nigeria, 330 Escherichia coli strains isolated from 187 children with diarrhea and 144 apparently healthy controls were examined for virulence traits. Based on the results of colony blot hybridization, strains were categorized as enteropathogenic E. coli (1.8%), enterotoxigenic E. coli (2.4%), enteroinvasive E. coli (1.2%), enterohemorrhagic E. coli (0.6%), enteroaggregative E. coli (10.3%), diffusely adherent E. coli (7.9%), cell-detaching E. coli (6.9%), and cytolethal distending toxin-producing E. coli (0.9%). E. coli strains that hybridized with a Shiga toxin gene probe but lacked other characteristics usually present in enterohemorrhagic E. coli constituted 8.4% of the isolates. Ninety-seven E. coli isolates adhered to HEp-2 cells in an aggregative fashion but did not hybridize with any of the probes employed in the study. Overall the pathotypes, apart from cytolethal distending toxin-producing E. coli, were recovered both from children with diarrhea and from children without diarrhea, though to a lower extent from the healthy children. All diarrheagenic E. coli strains were associated with diarrhea (P < 0.02). Heat-stable-enterotoxin-producing enterotoxigenic E. coli showed significant association with diarrhea (P < 0.02), as did strains that demonstrated aggregative adherence to HEp-2 cells (P < 0.04), but not those that hybridized with the CVD432 enteroaggregative probe.